MARKET VALUE ADDED (MVA), NILAI TUKAR RUPIAH, DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BEI - Murniati, Aniek (RISTANSI: Riset Akuntansi, 2024)
This research aims to examine the impact of Market Value Added (MVA), the rupiah exchange rate, and accounting profits on stock returns for telecommunications companies listed on the Indonesia Stock Exchange (BEI). MVA serves as a measure of the market value added by the company, reflecting its contribution to shareholder wealth. Additionally, the rupiah exchange rate, linked to macroeconomic conditions, can affect the financial performance of companies. The study also investigates the influence of accounting profits on stock returns, highlighting the significance of financial information in investment decision-making. An in-depth analysis of these factors is expected to provide valuable insights into the determinants of stock performance for telecommunications firms in the Indonesian capital market.